Screening tools for work-related musculoskeletal symptoms among workers: A rapid review of the literature - Esteban Portilla-Rojas; Laura Daniela Puche-Varón; Daniela Rivera-Guevara; Sebastián Rebolledo-Del Toro; Francisco Palencia-Sánchez (Interdisciplinary Journal of Epidemiology and Public Health)
Background: Work-related musculoskeletal disorders (WRMD) is a public and occupational health problem as it increases costs, absenteeism, and productivity loss. Identifying work-related risk factors for development of WRMD through screening tools is essential to determine and preventively treat patients. The objective of this study is to synthesis and evaluate the available screening tools for WMSD in the working population.